Спільне та відмінне у перекладацьких процесах у Великій і Західній Україні в 1920–1930-ті рр. - Коломієць, Лада Володимирівна; Kolomiyets’, L. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті зіставлено сприятливі та несприятливі чинники розвитку перекладацького процесу в 19201930-ті рр. у Великій та Західній Україні, які були розділені до 1939 р. політичним кордоном. Доведено, що під час ко-роткого періоду українізації художній переклад у радянській Україні переживав свій розквіт разом з іншими формами вербального та невербального мистецтва. Зокрема випущено сотні перекладних книжок, включаючи багатотомники та перевидання. Період «активної українізації», проголошений Всесоюзною комуністичною партією більшовиків 1923 р., тривав до 1929 р. Хоч його і швидко згорнули, процес українізації в радянській Україні мав значний вплив на всі сфери культурного життя, його сприятливі наслідки відчувалися до кінця 1930-х рр., незважаючи на те, що більшовики практично згорнули політику підтримки української мови ще в 1929 р. Подальше засудження й переслідування політики підтримки національної мови як «націоналістичної помилки» призведе до суворої цензури, публічних осудів, стане причиною смерті й забуття сотень українських громадських діячів, учених, письменників, а також перекладачів, зокрема й тих, хто переїхав до Радянського Союзу із Західної України, обдурений радянською пропагандою.  During a short period of the 1920s–1930s, literary translation in Ukraine experienced its heyday alongside with other forms of verbal and non-verbal art. Hundreds of books-in-translation were brought out, including multi-volume and reprinted editions. This period has gone down in the history of Ukrainian culture as the National Renaissance time. The period of ‘active Ukrainization’ proclaimed by the all-Union Communist Party of Bolsheviks in 1923, lasted till the year 1929. Aborted as it was, the process of Ukrainization in the Soviet Ukraine had greatly influenced all spheres of cultural life, and its favorable consequences survived until the late 1930s in spite of the fact that the Bolsheviks practically turned off the maintenance policy for the Ukrainian language in 1929. Further denunciation and condemnation of the national language-supportive policy as the ‘nationalistic fallacy’ would have brought about lots of rigid censorship, public conviction, death, and oblivion for the hundreds of Ukrainian public figures, scientists, and writers, as well as the translators among them, both from the USSR and from the Western Ukraine, who had been lured to move to the Eastern Ukraine by the Soviet propaganda. It is noteworthy that in the 1920-30s, which was the period of intense struggle for Ukrainian self-identity and survival, the Ukrainian intellectuals in the USSR and in the West, including those public leaders who then lived abroad as political emigrants, viewed translation as the gateway to European civilization and culture, a token of cultural adequacy of the Ukrainian people as a European nation. For many literary figures in the Eastern and Western Ukraine, separated from each other by the political boundary till 1939, translational practice served as a powerful guardian instrument aimed at the protection of the Ukrainian language from Russification and degradation. And by the late 1930s many of them have paid with their lives for their own indisputable literary and translation-related achievements. It had become typical of the late 1930s that the names of translators recently subjected to repressions simply disappeared from their newly published translations, as well as from many reprinted editions. All in all, most Ukrainian writers genuinely believed in the Ukrainization policy, and it was the national idea that inspired the rapid growth of literary translations in the National Renaissance period both in the Soviet and Western Ukraine. An outburst of political repressions against Ukrainian literati that had started in the late 1920s and topped out in 1937 didn’t succeed in quenching the accelerative development of the translation cause at once. The translated discourse created conjointly by the Easterners and the Galicians has become organically integrated into the national literary process.
Common and Different Features of Translation Processes in the Soviet and Western Ukraine in 1920–1930 s
Keywords: художній переклад; literary translation; політика українізації; policy of Ukrainization; національний ренесанс; National Renaissance